KONTROVERSI DAN SOLUSI: STRATEGI PEMASARAN SEKOLAH ISLAM DI TENGAH MASYARAKAT NON-MUSLIM - Kania Maharani Setyowati; Siti Aimah (CV. ADIBA AISHA AMIRA, 2026)
The research objectives in this study provide strategies in overcoming Islamic school marketing in a non-Muslim society. The object of this research is located at MTs Al-Ma'arif Badung Bali which operates in a non-Muslim community. The method used in this research is qualitative with a phenomenological approach. While collecting this data by means of observation, interviews and documentation. The data obtained were analyzed using an interactive model. This data analysis model consists of: data reduction, data presentation and conclusion drawing. The results of the discussion of this study are the Perceptions of Non-Muslim Communities towards Islamic Schools, namely that non-Muslim communities often have negative perceptions of Islamic schools due to fears of discrimination and lack of correct information, the influence of Social Media in Marketing Islamic Schools, namely social media plays an important role in providing relevant and reliable information for parents, as well as assisting schools in delivering their marketing messages more effectively and inclusively, and Collaboration between schools is very influential in increasing understanding and respect for differences, which shows the effectiveness of collaborative projects in reducing conflict and improving relationships between students